Three newly recorded genera from China (Hymenoptera, Braconidae, Opiinae), with the notes on the genus Neopius and descriptions of three new species - Sheng, Ying-Yi; Wu, Qiong; van Achterberg, Cornelis; Chen, Xue-Xin (Zootaxa, 2019)
The genera Bitomoides van Achterberg, 2004, Neopius Gahan, 1917 and Sternaulopius Fischer, 1965 of the subfamily Opiinae are newly discovered in China and one new species of each genus are described and illustrated, viz. Bitomoides platyaulicis Sheng & Chen sp. n., Neopius citrinus Sheng & Chen, sp. n. and Sternaulopius macrophthalmos Sheng & Chen sp. n. The status of the genus Neopius Gahan is discussed.